Farid to get down to business: Barisan candidate: I want to promote entrepreneurship in Pulau Betong - Marzukhi, Hafiz (The Star, 2013)
HAVING served two terms as the Pulau Betong state assemblyman, incumbent Muhamad Farid Saad is raring to go with his plans to create more entrepreneurs in the state constituency.